2016
DOI: 10.1111/1753-0407.12460
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between limited joint mobility of the hand and diabetic foot risk in patients with type 2 diabetes

Abstract: The results demonstrate a correlation between LJM of the hand and foot risk. Diagnosis of diabetic hand is simple and non-invasive, and is thus a useful method for assessing the risk of diabetic foot in T2D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(117 reference statements)
0
8
0
1
Order By: Relevance
“…Furthermore, the economic burden of treatment for complications is so high [31]. In the several risk factors for foot ulceration with diabetes [4][5][6][7][8][9]22], recognition of diabetic neuropathy and PAD is especially important to prevent diabetic foot ulcer [3,10]. Early recognition and management of risk factors can prevent or delay adverse outcomes of diabetic foot [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the economic burden of treatment for complications is so high [31]. In the several risk factors for foot ulceration with diabetes [4][5][6][7][8][9]22], recognition of diabetic neuropathy and PAD is especially important to prevent diabetic foot ulcer [3,10]. Early recognition and management of risk factors can prevent or delay adverse outcomes of diabetic foot [32].…”
Section: Discussionmentioning
confidence: 99%
“…The IWGDF classification was used to categorized the risk of diabetic foot: group 0 (no neuropathy), group 1 (neuropathy), group 2 (neuropathy, vascular disease or deformity), and group 3 (previous ulcer) [21]. As previously reported, we thought patients in group 0 to be at "low risk" for foot ulceration, whereas those in groups 1-3 to be at "high risk" [22,23]. Foot ulcer was defined as a full-thickness skin defect associated with neuropathy and/or peripheral arterial disease (PAD) of the lower limbs that required >14 days for healing [21,24,25].…”
Section: Foot Risk Classification and Definition Of Foot Ulcermentioning
confidence: 99%
“…Retinopathy was assessed by chart review and graded as follows: no diabetic retinopathy, simple diabetic retinopathy, and proliferative diabetic retinopathy 23. Neuropathy was diagnosed using criteria for diabetic neuropathy proposed by the Diagnostic Neuropathy Study Group 24.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we identified that NLR correlated with LJM of hand in patients with type 2 diabetes. LJM of hand, which is associated with diabetic micro- [1][2][3][4]7] and macrocomplications [8,9,40], is relatively easy to notify; however, clinicians often overlook this complication of diabetes in clinical situations [6]. NLR, which calculated simply and easily in routine clinical practice, could be used as a marker of diabetic complications including LJM of hand.…”
Section: Discussionmentioning
confidence: 99%